2015
DOI: 10.18632/oncotarget.4327
|View full text |Cite
|
Sign up to set email alerts
|

Structurally diverse c-Myc inhibitors share a common mechanism of action involving ATP depletion

Abstract: The c-Myc (Myc) oncoprotein is deregulated in a large proportion of diverse human cancers. Considerable effort has therefore been directed at identifying pharmacologic inhibitors as potential anti-neoplastic agents. Three such groups of small molecule inhibitors have been described. The first is comprised of so-called “direct” inhibitors, which perturb Myc's ability to form productive DNA-binding heterodimers in association with its partner, Max. The second group is comprised of indirect inhibitors, which larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 77 publications
5
65
1
Order By: Relevance
“…However, MYC inhibition strategies have been developed based on interrupting protein–protein interactions with MAX to abolish MYC‐dependent transcriptional activity . As a proof of concept, we demonstrated that MYC inhibitors blocked FGF2‐induced cell proliferation in vitro in MCF‐7 and T47D cells, this inhibition occurred even at concentrations lower than those reported to block cell proliferation in other cell lines, underscoring the exquisite sensitivity of these models . For in vivo assays, we used the C4‐HI murine model in which we have already demonstrated that its hormone‐independent growth relies on stromal FGF2 .…”
Section: Discussionmentioning
confidence: 91%
“…However, MYC inhibition strategies have been developed based on interrupting protein–protein interactions with MAX to abolish MYC‐dependent transcriptional activity . As a proof of concept, we demonstrated that MYC inhibitors blocked FGF2‐induced cell proliferation in vitro in MCF‐7 and T47D cells, this inhibition occurred even at concentrations lower than those reported to block cell proliferation in other cell lines, underscoring the exquisite sensitivity of these models . For in vivo assays, we used the C4‐HI murine model in which we have already demonstrated that its hormone‐independent growth relies on stromal FGF2 .…”
Section: Discussionmentioning
confidence: 91%
“…cancer cells or T cells) we find a transient increase in c-Myc following influenza infection (Figure 3E). c-Myc inhibitor a well-described direct inhibitor of c-Myc, also known as 10058-F4 (Calbiochem, Billerica MA), was used to determine if blocking c-Myc could restore normal metabolic phenotype (Hammoudeh et al, 2009; Rahl et al, 2010; Wang et al, 2015; Yin et al, 2003). Indeed, while the inhibitor alone increased bioenergetics, in the context of IAV infection c-Myc inhibitor reduced both ECAR and OCR to near normal levels in a dose dependent manner that were significantly lower than infection alone (Figure 3F–G).…”
Section: Resultsmentioning
confidence: 99%
“…It can promote cell proliferation, cell-cycle progression, survival and apoptosis resistance [46]. Several of these genes have been indentified, including cyclin D1, Bcl-2 and c-Myc [38,[47][48][49][50][51]. Our results show that BRD4 silencing by targeted shRNAs led to c-Myc downregulation in 786-O cells.…”
Section: Discussionmentioning
confidence: 64%